Enhancement of discus technique through combination discus drills (Coaching Track & Field Athletics)
Drills to improve discus technique are a useful tool in the track and field coaches arsenal. The difficulty with this is that discus throwing is not an isolated movement. It is a sequence of movements that allows the athlete to progressively apply greater force to the discus. Therefore some have called into question the use of drills and their genuine transfer to the discus technique.